Pregnant women's knowledge of birth defects and their associated factors among antenatal care attendees in referral hospitals of Amhara regional state, Ethiopia, in 2019 - Addisu Andualem Ferede; Belayneh Ayanaw Kassie; Kiber Temesgen Mosu; Worku Taye Getahun; Birhan Tsegaw Taye; Melaku Desta; Mamaru Getie Fetene (Frontiers Media S.A., 2023)
BackgroundBirth defects (BDs) are structural, behavioral, functional, and metabolic disorders present at birth. Due to lack of knowledge, families and communities stigmatized pregnant women following the birth of a child with birth defects. In Ethiopia, there was limited evidence to assess the level of knowledge among pregnant women despite increasing magnitude of birth defects.ObjectivesThis study aims to assess pregnant women's knowledge of birth defects and its associated factors among antenatal care (ANC) attendees in referral hospitals of Amhara regional state in 2019.Materials and methodsBetween 1 June and 30 June 2019, 636 pregnant women receiving prenatal care participated in an institution-based cross-sectional study. The approach for sampling was multistage. A semi-structured pretested interviewer-administered questionnaire was used to collect data. Data were entered in EpiData version 4.6 and analyzed using SPSS version 25 software. A bivariable and multivariable logistic regression model was used. Odds ratio with 95% confidence interval and p-value of ≤0.05 declared statistical significance association.ResultsA total of 636 pregnant women were included in the analysis. Accordingly, pregnant women's knowledge of birth defects was found to be 49.2% (95% CI: 45.4-53.1). Age group of <25 years (AOR = 0.16, 95% CI: 0.04-0.61), urban residence (AOR = 6.06, 95% CI: 2.17-16.94), ANC booked before 20 weeks of gestational age (AOR = 3.42, 95% CI: 1.37-8.54), and ever heard on birth defects (AOR = 5.00, 95% CI: 1.87-13.43) were significantly associated factors with pregnant women's knowledge of birth defects.ConclusionsApproximately half of the pregnant mothers were aware of birth defects. Addressing pre-pregnancy and pregnancy health information and education particularly on the prevention of birth defects is recommended.